Bronchoesophageal Fistula due to Esophageal Tuberculosis - Pathik Desai; Prachi Mayenkar; Thomas F. Northrup; Vijaya Mallela (Case Reports in Infectious Diseases)
This is a case report regarding a patient who presented with 6 months of dysphagia and subsequent 40-pound weight loss. The patient underwent imaging, suggestive of pulmonary TB. Further workup of his dysphagia with esophagogastroduodenoscopy and bronchoscopy revealed two bronchoesophageal fistulas. Tuberculosis is an important differential diagnosis of prolonged dysphagia in immunocompetent patients.